miR-155 Regulates the Proliferation of Glioma Cells Through PI3K/AKT Signaling - Wu, Dahao; Wang, Changzhen (Frontiers in Neurology, 2020)
Objective: Micro-RNA plays a critical role in the pathological process of gliomas. Previous research showed that the level of miR-155 was significantly increased in many cancers, including gliomas. However, the mechanism of glioma is still unknown. Method: To investigate the regulatory function of miR-155 on glioma U87-MG cells and its effects on related signaling pathways. After transfection of miR-155 mimic and inhibitor，the level of miR-155 were applied to detect cell proliferation, apoptosis, senescence index, invasive ability and cell migration at different time points (0h, 24h, 24h, respectively) by CCK8 assay, flow cytometry, β-galactosidase (β-gal) staining, transwell and scratch test, respectively. The effect of miR-155 on PI3K/AKT signal pathway was observed at meantime. Results: Compared with the control group, after miR-155 mimic transfection, U87-MG cell viability, cell migration rate and invasiveness were increased, while apoptosis and senescence were significantly decreased, which was the opposite on miR-155 inhibitor transfection. The phosphorylation levels of miR-155, PI3K, AKT , PI3K and AKT in U87-MG cells intervened with miR-155 mimic also increased significantly, while the levels of PTEN, Caspase-3, Caspase-9 mRNA and protein declined significantly, with statistically significant difference. Meanwhile, compared with the control group, miR-155 inhibitor group were on the contrary. Conclusion: The study indicated that miR-155 take charge a key function in regulating the proliferation, migration and invasion of glioma U87-MG cells through PI3K/AKT signaling pathway, and has anti-glioma effects by inhibition of miR-155, which provided ideas for further clinical treatment of glioma patients.